La unidad de la formación sacerdotal: Relación entre el período inicial y la formación permanente (Teología, 2020)
Following the article published in 2009, Mgr. Carmelo Giaquinta offers a reflection on priestly formation in the light of the decree Presbiterorum Ordinis of Vatican II and the Post-Synodal Apostolic Exhortation Pastores dabo vobis. The themes treated this time are: Baptism, the unity of priestly formation, the Seminary as an educational community, the Seminary as a community in the Church, Holy Orders as a sacrament of communion and the molding of the Pastor as someone entirely devoted to God and his people. It concludes with a keen consideration of the seminarian as a “future presbyter”.
Keywords: Priestly Formation; Presbiterorum Ordinis; Pastores davo vobis